The Role of the Public Prosecutor in Prosecuting Suspects of Drug Abuse Criminal Acts in Bone Regency - Suriyati, Suriyati; Rasyid, Mukhawas; Sari, Nurmi (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Drug abuse is categorized as an Extra Ordinary Crime due to its serious threat to national security. This study aims to examine the role of Public Prosecutors in prosecuting drug crime suspects in Bone Regency. Using an empirical research approach, the study was conducted through field research at the Watampone District Attorney's Office, focusing on the prosecutors' responsibilities in handling narcotics cases. The findings reveal several key roles of public prosecutors: receiving and reviewing case files after police investigations to determine completeness (P-21); accepting the suspect and evidence during Stage II; and prosecuting the suspect in court. In the courtroom, the prosecutor prepares indictments based on evidence and facts from investigations and must convincingly prove the suspect's guilt under relevant provisions of the Narcotics Law. The study also identifies key obstacles faced by public prosecutors, including weak coordination between law enforcement institutions such as the Police, BNN, and Customs, which often hinders information sharing and evidence alignment. Additionally, the limited understanding of evolving technologies and methods used by drug syndicates presents further challenges in effectively prosecuting such cases. The study concludes that strengthening inter-agency cooperation and enhancing the technical knowledge of prosecutors are essential steps to improve the prosecution process in drug-related crimes.